IDNLearn.com: Your one-stop destination for finding reliable answers. Join our community to receive timely and reliable responses to your questions from knowledgeable professionals.

Is x = 6 a solution to the equation 5(x – 3) = x + 13?
Follow the steps to find out.
1. Rewrite the equation 5(x – 3) = x + 13 with 6 substituted for x. Write a question mark over the equal sign to show that you're testing to see if the equation is true.

ill give brainliest


Sagot :

Yes, both equations will always work, but yes, at times it is more logical to use one over the other. for instance:

x-4y=6

x+4y=12

we see here that elimination would best fit:

x+x+4y-4y=6+12

or:

x=2y-3

7x+3y-81=23

substitute (2y-3) for x.

Also, once you have a single placeholder, put it ito quadratic form (ax^2+bx+c=0)

and use the quadratic formula:

x=(-b±sqrt(b^2-4ac))/2a

Answer:

yes

Step-by-step explanation:

Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.